2010
DOI: 10.1002/chem.201001211
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray Fluorescence Investigation of Ordered Intermetallic Phases as Electrocatalysts towards the Oxidation of Small Organic Molecules

Abstract: The composition of ordered intermetallic nanoparticles (PtBi and PtPb) has been quantitatively studied by in situ X-ray fluorescence (XRF) during active electrochemical control in solutions of supporting electrolyte and small organic molecules (SOMs). Because the Pt L(β1,2) lines and the Bi L(α1,2) lines are only separated by 200 eV, an energy-dispersive detector and a multiple-channel analyzer (MCA) were used to record the major fluorescent emission lines from these two elements. The molar ratios of platinum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…Low-energy electron diffraction (LEED) and Auger electron spectroscopy (AES) studies of the PtBi (001) surface after electrochemical cycling studies in H 2 SO 4 revealed a stable platinum-terminated surface and a higher tendency to surface oxidation with respect to elemental platinum . This was assigned as being responsible for the increased CO oxidation activity of PtBi in agreement with earlier studies. , In situ EXAFS/XANES and GI-XRD investigations on nanoparticulate PtBi and PtPb proved dissolution at even lower potentials than was concluded formerly, but could also show that a kinetic stabilization of +0.4 V takes place in the presence of fuel molecules. This effect could also be observed in a different study on a mixture of PtBi and platinum, which is reported to be more stable against Bi leaching than the single-phase intermetallic compound, due to adsorbed CO on the Pt sites. , Another contribution focuses on the synthesis of differently shaped PtBi nanoplatelets, which were also used for formic acid oxidation .…”
Section: Electrooxidationsupporting
confidence: 88%
“…Low-energy electron diffraction (LEED) and Auger electron spectroscopy (AES) studies of the PtBi (001) surface after electrochemical cycling studies in H 2 SO 4 revealed a stable platinum-terminated surface and a higher tendency to surface oxidation with respect to elemental platinum . This was assigned as being responsible for the increased CO oxidation activity of PtBi in agreement with earlier studies. , In situ EXAFS/XANES and GI-XRD investigations on nanoparticulate PtBi and PtPb proved dissolution at even lower potentials than was concluded formerly, but could also show that a kinetic stabilization of +0.4 V takes place in the presence of fuel molecules. This effect could also be observed in a different study on a mixture of PtBi and platinum, which is reported to be more stable against Bi leaching than the single-phase intermetallic compound, due to adsorbed CO on the Pt sites. , Another contribution focuses on the synthesis of differently shaped PtBi nanoplatelets, which were also used for formic acid oxidation .…”
Section: Electrooxidationsupporting
confidence: 88%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17] In electrocatalysis research, some intermetallic compounds have already showed striking effects. [5][6][7][8][9][10][11][12][13][18][19][20][21][22][23][24][25][26][27][28][29] For instance, intermetallic PtPb, PtBi, PtIn and Pt 3 Ti were identified to have superior activity toward the oxidation of small organic molecules in comparison to disordered alloys. 5,8 Among intermetallic compounds, the Au-Cu system has been well understood and is often used as a model for new synthetic study.…”
Section: Introductionmentioning
confidence: 99%
“…Bearing in mind dissolution of Bi in acidic solution when cycling up to 0.8 V and beyond [10] but also stability of PtBi intermetallics in the presence of formic acid [23,24], in order to examine the unusual electrochemical behavior of our Pt@Bi/GC electrode in formic acid oxidation, two additional experiments were performed and shown in Fig. 2.…”
Section: Formic Acid Oxidationmentioning
confidence: 99%
“…Although it has been shown that the ordered PtBi intermetallic phases are not stable to the application of moderate to high positive potentials in the acid medium due to Bi leaching from the matrix and dissolution when the electrode is subjected to cycling up to +0.80 V (Ag/AgCl) or beyond [10,22,23], studies of PtBi catalysts signify their stability in the presence of formic acid. Namely, kinetic stabilization of the PtBi electrode surface is due to the competition between the oxidation of formic acid at the electrode/solution interface and Bi leaching, i.e., corrosion/oxidation process [23,24]. The relationship between the leaching potentials and the stability of the catalytic activity of different Pt-based catalysts was elucidated by applying the cycling potential [23,25], pulsing [26], or constant electric potential treatment over the electrodes [12].…”
Section: Introductionmentioning
confidence: 99%